The Effect of the Covid-19 Pandemic on the Economy of Micro, Small and Medium Enterprises (MSMEs) in Sinarsari Village, Dramaga District, Bogor Regency - Rahmawati, Yeni; Jaelani, Alan (Jurnal Pengabdian Nusantara, 2023)
Since the initial announcement of Covid-19, MSMEs have become one of the worst and most affected sectors until the emergence of the PSBB and also the new normal. Many MSME business actors experience vulnerability, go out of business, and are only able to survive for a certain period, so the negative impact during the Covid-19 pandemic always accompanies the journey of MSMEs. In addition, various negative impacts during the Covid-19 pandemic have received the attention of various parties to be able to prevent and deal with problems faced by MSMEs during the Covid-19 pandemic. This study will describe the condition of MSMEs and the impact of Covid-19 on the MSME economy in Sinarsari village, Dramaga district, Bogor. This study used a qualitative approach with a descriptive research type, and data collection was carried out using deep interviews. From the results of research and analysis that have been carried out, it is known that the Covid-19 pandemic hurts the vulnerability of MSMEs in Sinarsari village. In addition, the Covid-19 pandemic has also had an impact on the decline in the economy of MSMEs in Sinarsari village, as well as affecting changes in the conditions for MSME business actors to trade with e-commerce and digital marketing to be able to survive and thrive in the face of change.